1992
DOI: 10.1177/000348949210101201
|View full text |Cite
|
Sign up to set email alerts
|

Indium 111–Labeled Leukocyte Scintigraphy in Evaluating Head and Neck Infections

Abstract: This retrospective study looked at the role of indium 111-labeled white blood cell (111In WBC) scintigraphy in head and neck infections. The efficacy of 111In WBCs was compared to gallium 67 citrate (67Ga) and technetium Tc99m methylene diphosphonate (99mTc MDP) scintigraphy in detecting and monitoring the resolution of infection. For 22 active infections, the sensitivities for 111In WBC, 67Ga, and 99mTc MDP scintigraphy were 94%, 56%, and 86%, respectively, and the specificities for 111In WBC, 67Ga, and 99mTc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The Ga‐67 scan has been used to evaluate the resolution of established osteomyelitis. Ga‐67 scans, however, often take up to 6 months to return to normal after successful treatment of osteomyelitis 24 . Ga‐67 scans were not obtained in our patients, so comparisons could not be made.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The Ga‐67 scan has been used to evaluate the resolution of established osteomyelitis. Ga‐67 scans, however, often take up to 6 months to return to normal after successful treatment of osteomyelitis 24 . Ga‐67 scans were not obtained in our patients, so comparisons could not be made.…”
Section: Discussionmentioning
confidence: 90%
“…Epstein et al 24 recently reported planar In‐WBC scintigraphy as a useful technique for diagnosis and monitoring of osteomyelitis. However, false‐negative and false‐positive In‐WBC scans have been reported in low‐grade or chronic infections, at sites with extensive bone marrow (such as the vertebral column), or in immunosuppressed patients, inpatients after long‐term intravenous antibiotic therapy, and inpatients with diabetic microangiopathy 22‐29 . By combining SPECT Tc‐99m‐MDP bone with In‐WBC SPECT scintigraphy, many of the problems inherent with planar In‐WBC scintigraphy can be avoided.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our experience with SPECT in this population is limited due to the low incidence of this disease, but these preliminary results demonstrate the possibility of detection of deep‐seated bone involvement. The low sensitivity of Ga 67 scintigraphy as described by Epstein et al 12 can be explained in that SPECT was not used in all patients. The initial interpretation in this study was done on planar images.…”
Section: Discussionmentioning
confidence: 99%